ANALYSIS OF LISTENING STRATEGIES OF CLASS XII STUDENTSAT MAN 1 LAMPUNG SELATAN - Rosanti, Ika Ratna; Tauhid, Tauhid (STIT AL MULTAZAM, 2023)
This research aims to determine the listening strategies applied by students in learning listening skills at MAN 1 Lampung Selatan. The research design used in this research is qualitative descriptive research using research instruments in the form of observation, interviews and field notes. The participants in this research were 10 class XII students at MAN 1 Lampung Selatan, and in selecting this sample the researcher used purposive sampling. The students were considered capable participants in this study because they had learned more complex listening skills compared to first and second grade. Based on the research results, it is known that students are asked to play the audio more than once, if they hear unfamiliar or doubtful vocabulary, they write it down and ask the teacher or friends about the vocabulary, both teachers and students provide feedback about the listening skills they have learned. Several media that they use to practice their listening skills such as videos, films, audio and music. From the results of interviews with students, it was also found that students practice their listening skills when they have free time and students want to master English because they want to implement the knowledge they learn in everyday life and based on this it is known that the listening strategies that students apply in learning skills listening at MAN 1 Lampung Selatan is a cognitive strategy and a social affective strategy.